Exploring the adolescents’ career development and career-related teacher support: the NEFELE career guidance model - Parola, Anna; Diano, Federico; Ponticorvo, Michela; Sica, Luigia Simona (Frontiers in Psychology, 2024)
In today’s dynamic landscape, navigating career paths in the midst of economic, societal, and technological changes has become increasingly challenging. The developmental psychology studies (see the career construction theory framework, CCT, Savickas, 2012) and European educational standards consistently support the crucial role of teachers in supporting students' career choices. However, teachers do not seem to be trained for this role, and the NEFELE project aims to fill this gap. The training model proposed in this paper aims to provide teachers with the knowledge and tools to support their students' career choices in educational systems. Using a randomized control trial, a study was conducted in the Italian context involving 8 teachers and their classrooms. Pre- and post-test measurements were carried out to study the effectiveness of the intervention. Students in the experimental group who participated in career guidance activities taught by teachers trained through the NEFELE training model show an increase in career-related teacher support, career adaptability, career explorations, and career competences. Implications for practice are discussed.